Identity construction and self-modelling in celebrity culture. The emotional costs of reputation and social sharing - Rando, Laura (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Reflexivity and the need for recognition are fundamental in the construction of identity and self-perception and thus in the foundational aspects of reputation. I intend to develop some critical reflections on the emotional costs that celebrity culture and social sharing entail for the individual in the face of the pervasiveness of social media in the private and public sphere.